Paul Bunyan - Sabin, Louis; Illustrated by Smolinski, Dick (New Jersey Troll Associates, 1985)
Presents some of the extravagant feats of the greatest logger of all time, Paul Bunyan.
Include Color Illustrations
Keywords: Bunyan, Paul (Legendary character)